# Elimantation

Discussion in 'Math' started by Steve1992, Sep 8, 2012.

1. ### Steve1992 Thread Starter Senior Member

Apr 7, 2006
100
0
Vc - Vo = I1Rf

Vcc - Vc = (I1 + I2)R1 (2)

Vc-(-Vcc) = Vc + Vcc = I2R2

Elimate I1 and I2 from the above equation and show that:

Vcc - Vc = (Vc - Vo)R1/Rf + (Vc + Vcc)R1/R2

I understand that I1 and I2 are replaced from (2) with (Vc - Vo) and (Vc + Vcc) but how does /Rf and /R2 slot in?

Thanks

2. ### panic mode Senior Member

Oct 10, 2011
1,328
305
you have I1 in

Vc - Vo = I1Rf

which can be expressed as

I1=(Vc - Vo)/Rf

same should apply for getting I2 from some other equation like
Vc + Vcc = I2R2

I2=(Vc + Vcc)/R2

then you replace I1 and I2 in (2) to get result

Steve1992 likes this.
3. ### WBahn Moderator

Mar 31, 2012
18,085
4,917
I don't think you do understand it, because it isn't true. I1 and I2 are currents while (Vc-Vo) and (Vc+Vcc) are voltages; you can't just replace one with the other. Hopefully panic mode's suggestion has cleared things up for you.